2024
DOI: 10.1098/rsos.231529
|View full text |Cite
|
Sign up to set email alerts
|

Shift in virus composition in honeybees ( Apis mellifera ) following worldwide invasion by the parasitic mite and virus vector Varroa destructor

Vincent Doublet,
Melissa A. Y. Oddie,
Fanny Mondet
et al.

Abstract: Invasive vectors can induce dramatic changes in disease epidemiology. While viral emergence following geographical range expansion of a vector is well known, the influence a vector can have at the level of the host's pathobiome is less well understood. Taking advantage of the formerly heterogeneous spatial distribution of the ectoparasitic mite Varroa destructor that acts as potent virus vector among honeybees Apis mellifera , we investigated the impact of its re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 109 publications
(176 reference statements)
0
5
0
Order By: Relevance
“…In varroa-free populations, common honeybee pathogens, including DWV, frequently occur at low prevalence with low viral titres [ 21 , 23 , 25 , 27 , 36 ] or are mostly absent, such as in Australia [ 29 ]. The rapid and dramatic increase in DWV frequency and titre in the honeybee’s native community following the Ushant invasion highlights the importance of varroa control and mirrors the effects observed in non-native populations in New Zealand [ 21 ] and Hawai’i [ 27 ], and fits with the long-term pattern observed in European islands [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In varroa-free populations, common honeybee pathogens, including DWV, frequently occur at low prevalence with low viral titres [ 21 , 23 , 25 , 27 , 36 ] or are mostly absent, such as in Australia [ 29 ]. The rapid and dramatic increase in DWV frequency and titre in the honeybee’s native community following the Ushant invasion highlights the importance of varroa control and mirrors the effects observed in non-native populations in New Zealand [ 21 ] and Hawai’i [ 27 ], and fits with the long-term pattern observed in European islands [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The re-emergence of DWV and its global spread followed varroa's host switch to western honeybees [8,18]. In addition, there are multiple other honeybee viral pathogens that are vectored by varroa [19] and that have also been shown to increase in prevalence in the presence of this vector, such as acute bee paralysis virus (ABPV), black queen cell virus (BQCV) and slow bee paralysis virus (SBPV) [19][20][21][22][23]. Although varroa uniquely parasitizes honeybees, its effect as a vector is not limited to honeybees.…”
Section: Introductionmentioning
confidence: 99%
“…The primers and probe systems previously described for the detection of honeybee viral pathogens ABPV, BQCV, DWVA, DWVB, CPBV and SBV [25,26,29,[31][32][33][34][35][36][37][38][39] were tested for their specificity and inclusivity by BLASTN (https://blast.ncbi.nlm.nih.gov/Blast.cgi, accessed on 27 April 2024) against 500 database entries. Those matching the highest number of sequences of the target virus were selected for use in one-step RT-qPCR tests with TaqMan probes.…”
Section: Oligonucleotide Selection/designmentioning
confidence: 99%
“…ABPV, DWVA and DWVB are transmitted by V. destructor [ 2 ]. Moreover, it was reported that V. destructor mite presence was significantly associated with a higher prevalence of BQCV, CBPV and SBV [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation